Current Situation of the State-Confessional Relations in the Republic of Kazakhstan (on the example of Roman Catholic Church) - Smagulov, Nurlan (Journal of Sociology: Bulletin of Yerevan University, 2012)
The article presents the very important issue of relations between state and religious bodies in the multinational societies. The society of Kazakhstan consisting of more than 120 ethnic groups and 40 religious communities represents an example of current relations between state bodies and church institutions within the concepts of coexistence and development. The author discusses these issues on the example of the Roman Catholic Church, demonstrating the historical developments and the current situation. The main idea of the article is in the cooperation of the state – society – church towards peaceful coexistence and development of human values based on the state development strategy and common interests.